Community Structure of Zooplankton in the waters of Kampung Ambong Likupang, North Minahasa - Rizki Antuke; Gaspar D. Manu; Rose O. S. E. Mantiri; Fransine B. Manginsela; Adnan S. Wantasen; Deiske A. Sumilat (Sam Ratulangi University, 2020)
Zooplankton has an important role as a linking chain between primary producers and biota at higher trophic levels. This organism is a component in the food chain that has a dual role as both the first consumer and the second consumer. They are intermediaries between plankton and nekton groups. This research was conducted at the field station of Fisheries and Marine Sciences Faculty of Sam Ratulangi University, which is located in Kampung Ambong, Likupang, North Minahasa Regency, to identify the species and to determine the structure of the Zooplankton community through: Density, Relative Density, Diversity (H '), Dominance (e ), and Uniformity (C). Based on the results of species identification, 20 species from 15 genera in 3 classes were obtained, namely Hexanauplia (13 genus 18 species), Crustacea (1 genus 1 species), and Malacostraca (1 genus 1 species). The results of the community structure analysis obtained moderate uniformity values at points 1, 2, and 3. The dominance index shows low values at all three points, where point 2 C = 0.17 and at points 1 and 3 C = 0.20 This means that there is no types of plankton that dominate the area. Temperature 28 ° C, Salinity 300/00, and pH = 7 indicate conditions that are still in a good range as a place to live and grow Zooplankton.Keywords: Zooplankton; Diversity; Community Structure; LikupangAbstrakZooplankton mempunyai peran penting sebagai rantai penghubung produser primer dengan biota pada tingkat trofik yang lebih tinggi, juga merupakan salah satu komponen dalam rantai makanan yang berperan ganda baik sebagai konsumen tingkat pertama maupun konsumen tingkat ke dua, selanjutnya merupakan penghubung antara plankton dan nekton. Penelitian ini dilakukan di Laboratorium Basah Fakultas Perikanan dan Ilmu Kelautan Universitas Sam Ratulangi, Kampung Ambong, Likupang, Kabupaten Minahasa Utara, untuk mengetahui jenis dan struktur komunitas Zooplankton melalui: Kepadatan, Kepadatan Relatif, Keanekaragaman (H’), Dominansi (e), dan Keseragaman (C). Berdasarkan hasil Identifikasi jenis, diperoleh 20 spesies dari 15 genus dalam 3 klas, yaitu Hexanauplia (13 genus 18 spesies), Crustacea (1 genus 1 spesies), dan Malacostraca (1 genus 1 spesies). Hasil analisis struktur komunitas diperoleh nilai keseragaman yang sedang pada titik 1, 2, dan 3. Indeks Dominansi menunjukkan nilai yang rendah pada ketiga titik, dimana titik 2 C = 0,17 dan pada titik 1 dan 3 C = 0,20 Artinya tidak terdapat jenis plankton yang mendominsi daerah tersebut. Suhu 28°C, Salinitas 300/00, dan pH= 7 menunjukkan kondisi yang masih dalam kisaran baik sebagai tempat hidup dan bertumbuhnya Zooplankton.Kata kunci: Zooplankton; Keanekaragaman; Struktur Komunitas; Likupang